Development and Validation of a Serologic Test Panel for Detection of Powassan Virus Infection in U.S. Patients Residing in Regions Where Lyme Disease Is Endemic - Angela M. Thomm (American Society for Microbiology, 2018)
ABSTRACT Powassan virus (POWV) is an emerging tick-borne arbovirus presenting a public health threat in North America. POWV lineage II, also known as deer tick virus, is the strain of the virus most frequently found in Ixodes scapularis ticks and is implicated in most cases of POWV encephalitis in the United States. Currently, no commercial tests are available to detect POWV exposure in tick-borne disease (TBD) patients. We describe here the development and analytical validation of a serologic test panel to detect POWV infections. The panel uses an indirect enzyme immunoassay (EIA) to screen. EIA-positive samples reflex to a laboratory-developed, POWV-specific immunofluorescence assay (IFA). The analytical sensitivity of the test panel was 89%, and the limit of detection was a plaque reduction neutralization test (PRNT) titer of 1:20. The analytical specificity was 100% for the IgM assay and 65% for the IgG assay when heterologous-flavivirus-positive samples were tested. On samples collected from regions where Lyme disease is endemic, seroprevalence for POWV in TBD samples was 9.4% (10 of 106) versus 2% when tested with non-TBD samples (2 of 100, P = 0.034). No evidence of POWV infection was seen in samples collected from a region where Lyme disease was not endemic (0 of 22). This test panel provides a sensitive and specific platform for detecting a serologic response to POWV early in the course of infection when neutralizing antibodies may not be detectable. Combined with clinical history, the panel is an effective tool for identifying acute POWV infection. IMPORTANCE Approximately 100 cases of POWV disease were reported in the United States over the past 10 years. Most cases have occurred in the Northeast (52) and Great Lakes (45) regions (https://www.cdc.gov/powassan/statistics.html). The prevalence of POWV in ticks and mammals is increasing, and POWV poses an increasing threat in a greater geographical range. In areas of the Northeast and Midwest where Lyme disease is endemic, POWV testing is recommended for patients with a recent tick bite, patients with Lyme disease who have been treated with antibiotics, or patients with a tick exposure who have tested negative for Lyme disease or other tick-borne illnesses and have persistent symptoms consistent with posttreatment Lyme disease. Testing could also benefit patients with tick exposure and unexplained neurologic symptoms and chronic fatigue syndrome (CFS) patients with known tick exposure. Until now, diagnostic testing for Powassan virus has not been commercially available and has been limited to patients presenting with severe, neurologic complications. The lack of routine testing for Powassan virus in patients with suspected tick-borne disease means that little information is available regarding the overall prevalence of the virus and the full spectrum of clinical symptoms associated with infection. As Ixodes scapularis is the tick vector for Powassan virus and multiple other tick-borne pathogens, including the Lyme disease bacterium, Borrelia burgdorferi, the clinical presentations and long-term outcomes of Powassan virus infection and concurrent infection with other tick-borne disease pathogens remain unknown.